Auditoría financiera del pasivo al Jardín Botánico del Quindío, con referencia a los estados financieros con corte a 31 de diciembre del año 2010 (2011)
Implementation of international auditing standards (ISAs) and generally accepted auditing standards (NAGAS) in the execution of a financial audit of liabilities. Given the importance of financial audit within the framework of integrity, loyalty and fairness of the information provided in the financial statements of an organization is essential to develop a thorough review by examining the regulations governing this type of research, having as starting point the approach to the liability of the foundation of scientific research and environmental education from the QUINDIO Botanical Garden.